2019
DOI: 10.1123/pes.2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Biomarker Release After Exercise in Healthy Children and Adolescents: A Systematic Review and Meta-Analysis

Abstract: Purpose:The authors evaluated the impact of acute exercise and 24-hour recovery on serum concentration of cardiac troponins T and I (cTnT and cTnI) and N-terminal fragment of the prohormone brain natriuretic peptide (NT-proBNP) in healthy children and adolescents. The authors also determined the proportion of participants exceeding the upper reference limits and acute myocardial infarction cutoff for each assay.Method:Web of Science, SPORTDiscus, MEDLINE, ScienceDirect, and Scopus databases were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 79 publications
5
45
2
Order By: Relevance
“…As previously noticed in other studies [3,4], participants had normal ECG and reported no history of personal nor familiar cardiovascular disease. However, the overall rate of positive detection was substantial (25/36, 69.44%), and similar to that in a recent meta-analysis including studies with participants under the age of 18 (166/219, 75.8%, χ 2 = 0.37, p = 0.54) [6]. These findings reinforce the hypothesis that transient elevations of cTn after practicing sport might be a physiological acute response to exercise rather than a pathological sign of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As previously noticed in other studies [3,4], participants had normal ECG and reported no history of personal nor familiar cardiovascular disease. However, the overall rate of positive detection was substantial (25/36, 69.44%), and similar to that in a recent meta-analysis including studies with participants under the age of 18 (166/219, 75.8%, χ 2 = 0.37, p = 0.54) [6]. These findings reinforce the hypothesis that transient elevations of cTn after practicing sport might be a physiological acute response to exercise rather than a pathological sign of cardiovascular disease.…”
Section: Discussionsupporting
confidence: 86%
“…Blood samples were taken from an antecubital vein before exercise (pre) and at 3 h after exercise (post). The election of these sampling times was based on previous research reporting an approximate time-to-peak for cTnT of between 2 and 5 h after exercise [6]. Blood samples were quickly centrifuged and stored at −80 • C for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise has been reported as a very important factor in the maintenance of good health [31][32][33]. Todde et al [33] has suggested that high-intensity exercise and functional exercises can improve functional mobility and muscle endurance among those who are above the age of 65.…”
Section: Exercisementioning
confidence: 99%
“…Additionally in the acute phase, troponins, when elevated, do track with inflammatory and coagulation markers, suggesting non-specific cytokine-mediated cardiotoxicity [ 8 ]. On the other hand, in athletes, hs-troponins can be elevated even in absence of overt myocardial disease or injury, due to repeated exercise, especially in the young subjects [ 9 , 10 ].…”
mentioning
confidence: 99%